2021
DOI: 10.1186/s12882-021-02540-6
|View full text |Cite
|
Sign up to set email alerts
|

Renal angina index predicts fluid overload in critically ill children: an observational cohort study

Abstract: Background Fluid overload and acute kidney injury are common and associated with poor outcomes among critically ill children. The prodrome of renal angina stratifies patients by risk for severe acute kidney injury, but the predictive discrimination for fluid overload is unknown. Methods Post-hoc analysis of patients admitted to a tertiary care pediatric intensive care unit (PICU). The primary outcome was the performance of renal angina fulfillment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 40 publications
0
9
1
Order By: Relevance
“…Fluid overload is commonly associated with poor outcomes in critically ill pediatric patients with sepsis, with increased mortality, duration of mechanical ventilation, and hospital stay. 24,25 The RAI has shown an ability to predict the risk of developing fluid overload. 24 We believe that our study has a few limitations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fluid overload is commonly associated with poor outcomes in critically ill pediatric patients with sepsis, with increased mortality, duration of mechanical ventilation, and hospital stay. 24,25 The RAI has shown an ability to predict the risk of developing fluid overload. 24 We believe that our study has a few limitations.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 The RAI has shown an ability to predict the risk of developing fluid overload. 24 We believe that our study has a few limitations. It is a study of a single referral center, which cares for children with complex pathologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This group of patients is among the highest risk for significant fluid accumulation and the negative consequences of fluid overload. 31 We also found that mechanical ventilation alone demonstrated the highest accuracy among all patients, including those who were receiving no organ support. This may reflect that mechanical ventilation included those on chronic invasive mechanical ventilation and stable home-going ventilation, many of whom did not have IV access to receive IV fluids.…”
Section: Discussionmentioning
confidence: 54%
“…However, if the child's weight was 14 kg just 2 months ago at a well child visit and this was due to acute gastroenteritis, the definition of fluid overload at this point might not hold based on our common measurement methods (weight-based or metric-based) and the patients might reasonably be considered as a positive FB. There is not yet a standard approach to defining FB or fluid overload and from the nine pediatric-focused original research articles published from 2020 through March 2022 there were more than 12 different definitions with multiple additional combinations possible [ 2 ▪ , 3 , 4 ▪ , 5 ▪▪ , 6 , 7 ▪▪ , 8 , 9 ▪ , 10 ▪ ] (Table 1 ). The different definitions included metric vs. weight-based methods, considered different baseline (or anchor) weight, and different percentage thresholds (e.g., 10% vs. 20% vs. continuous).…”
Section: Fluid Balance and Fluid Overload: Definition And Measurementmentioning
confidence: 99%